A novel approach to the synthesis of the FG fragment of pectenotoxin-4 - Luscombe, KN (2012)
The cobalt-catalysed oxidative cyclisation of 5-hydroxy alkenes has been demonstrated to be a powerful synthetic tool for the formation of trans-THFs with excellent diastereoselectivity. This thesis describes the utilisation of this methodology in the synthesis of the FG fragment of pectenotoxin-4, allowing the scope of the reaction to be further explored. Introduction: This section introduces the pectenotoxins, a family of structurally complex closed-chain polyether macrolides with promising biological activities. The isolation, structural elucidation, and biological properties of the pectenotoxins are reviewed, along with a summary of previous syntheses towards the FG fragment of pectenotoxin-4. In addition, the cobalt-catalysed oxidative cyclisation of 5-hydroxy alkenes and its application in synthesis is discussed. Results and Discussion: An outline of the synthetic strategy employed in this project and details of the novel retrosynthesis of the C31-C40 fragment of pectenotoxin-4 is described. The synthetic studies carried out towards the synthesis of the FG fragment of pectenotoxin-4 are discussed in detail, with the exploitation of a cobalt-catalysed oxidative cyclisation as the key step to form the trans-THF F-ring. Overall, the FG fragment, which contains six stereogenic centres, was achieved in 18 total synthetic steps (13 longest linear sequence).